Livin/BIRC7 gene expression as a possible diagnostic biomarker for endometrial hyperplasia and carcinoma - Basma K. Elmekkawy; Rasha M. S. Shoaib; Amal K. Seleem; Dalia Shalaan; Entsar A. Saad (Journal of Genetic Engineering and Biotechnology, 2021)
Abstract Background Livin/BIRC7 is a member of the inhibitors of apoptosis proteins family which are implicated in development of cancer through the inhibition of apoptosis process. This case-control study was intended to investigate livin/BIRC7 gene expression in endometrial hyperplasia and carcinoma and its correlation to some oxidative stress markers in addition to its possible diagnostic performance. Methods This study included 90 participants [30 endometrial hyperplasia patients, 30 endometrial carcinoma patients, and 30 healthy controls]. Livin/BIRC7 gene expression was analyzed using quantitative reverse transcriptase-polymerase chain reaction (RT-PCR). Serum catalase activity was assessed by enzyme-linked immunosorbent assay (ELISA) and malondialdehyde level was measured by the colorimetric method. Results Livin/BIRC7 gene expression was significantly (p < 0.001) higher in endometrial carcinoma from patients with endometrial hyperplasia when compared to controls. A positive correlation was found between livin/BIRC7 expression and serum catalase activity and malondialdehyde level in endometrial hyperplasia and carcinoma. The detection of livin/BIRC7 in endometrial carcinoma has excellent sensitivity and specificity. Conclusions Livin/BIRC7 was overexpressed in endometrial carcinoma with excellent power to differentiate endometrial carcinoma from endometrial hyperplasia or healthy subjects, suggesting that it might be a useful molecular marker for endometrial carcinoma diagnosis.